The hydration ability of three commercially available sports drinks and water - Hill, Rebecca J.; Bluck, Leslie J.C.; Davies, Peter S.W. (Journal of science and medicine in sport, 2008)
This paper compares the hydration ability of three commercially-available sports drinks with water under conditions of rest and exercise, using a deuterium dilution technique. For the rest group, 0.05 g/kg of body weight of deuterium, contained in gelatine capsules, was ingested with one of the test solutions and saliva samples were collected every five minutes for an hour while the subject remained seated. The deuterium was administered as above for the exercise group but sample collection was during one hour of exercise on a treadmill at 55% of the subject's maximum heart rate. The enrichment data for each subject were mathematically modelled to describe the kinetics of hydration and the parameters obtained were compared across drinks using a basic Anova. At rest, significant differences were found for t 1, t 1/2, and the percent of drink absorbed at t 1. The differences between drinks were not significant for t 2 or the maximum absorption rate. For the exercise group, the only significant difference was found between water and the sports drinks at t 1. Therefore, we conclude that labelling with a deuterium tracer is a good measure of the relative rate ingested fluids are absorbed by the body. Because of the lack of differences found at t 2, which is indicative of the 100% absorption time, both at rest and during exercise, it may be speculated that, compared to water, the sports drinks studied in this paper did not hydrate the body at a faster rate.